(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of the study was to assess the incidence, types and risk factors of thyroid dysfunction and thyroid autoimmunity, and to correlate the laboratory parameters with clinical findings. Study Design: Prospective clinical trial Place and Duration of Study: This study was conducted at General hospital, Lahore from March, 2011 to December 2011. Materials and Methods: The study enrolled sixty diagnosed patients of chronic hepatitis C with normal baseline thyroid hormone levels (TSH, FT3, FT4). Anti-thyroid peroxidase antibodies (anti-TPO-Ab) were also assayed. Baseline results were compared with those obtained during and at the end of interferon-alpha (IFN- α) and ribavirin combination therapy. Results: Incidence of thyroid dysfunction was 10%. Six patients (10%) developed thyroid dysfunction. Subclinical hypothyroidism was more common. Four female patients developed hypothyroidism and 2 patients showed hyperthyroidism. The overall incidence of anti thyroid peroxidase antibodies (anti-TPO-Ab) before treatment was 1.7% which became 5% at the end of therapy. Conclusion: Female sex and anti-thyroid peroxidase antibodies (anti-TPO-Ab) either present before or during treatment at are at risk of developing thyroid dysfunction, so all the patients of chronic hepatitis C should be screened for thyroid functions and anti-thyroid peroxidase antibodies (anti-TPO-Ab) before treatment with interferon-alpha (IFN- α) & ribavirin combination therapy, and be monitored during and after treatment